1988
DOI: 10.1677/joe.0.1170075
|View full text |Cite
|
Sign up to set email alerts
|

The transport of plasma thyroxine in White storks (Ciconia ciconia) and the association of high levels of plasma transthyretin (thyroxine-binding prealbumin) with moult

Abstract: Antisera raised against domestic fowl transthyretin (thyroxine-binding prealbumin) and quail albumin were used to identify thyroxine-binding proteins in the plasma of White storks (Ciconia ciconia) and to measure seasonal changes in these proteins. Three plasma proteins were shown to bind thyroxine (T4). They were albumin, transthyretin and a protein with an electrophoretic mobility on non-denaturing polyacrylamide gel electrophoresis intermediate between albumin and transthyretin. There was no thyroxine-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…A short period of exposure, of approximately 30 min, is sufficient to trigger a nearly full thyroid hormone effect on plasma protein synthesis (Hertzberg et al, 1981). Results of another study demonstrated the existence of an association between increase in concentration of plasma transthyretin and molting in birds (Cookson et al, 1988). This carrier protein, also called thyroxine-binding preal-bumin, may be responsible for increase in prealbumin fraction during remige molt observed in our study.…”
Section: Discussionsupporting
confidence: 65%
“…A short period of exposure, of approximately 30 min, is sufficient to trigger a nearly full thyroid hormone effect on plasma protein synthesis (Hertzberg et al, 1981). Results of another study demonstrated the existence of an association between increase in concentration of plasma transthyretin and molting in birds (Cookson et al, 1988). This carrier protein, also called thyroxine-binding preal-bumin, may be responsible for increase in prealbumin fraction during remige molt observed in our study.…”
Section: Discussionsupporting
confidence: 65%